From practice employee to (co-)owner: young GPs predict their future careers: a cross-sectional survey. Issue 1 (December 2017) - Gisler, Luzia; Bachofner, Marius; Moser-Bucher, Cora; Scherz, Nathalie; Streit, Sven
Abstract Background In Switzerland, the mean age of GPs in 1993 was 46. In 2015, it had increased to 55, and GPs over 65 made up 15% of the workforce of the about 6000 GPs. As older, self-employed GPs retire, young doctors will be needed to fill their positions and eventually take over their practices. We set out to determine what kind of employment young GPs wanted, if they thought their preference would change over time, and the working conditions and factors most important in their choice of practice. Methods We administered a cross-sectional online survey to members of the Swiss Young General Practitioners Association (n = 443). Our survey relied on closed questions, ratings of attractiveness of fictional job ads, and an open question to capture participants' characteristics, and their preferred type of practice and working conditions. Results We received 270 (61%) replies. Most were women (71%) and wanted to work in the suburbs or countryside in small GP-owned group practices, with up to five colleagues. Most intended to work part-time: mean desired workload was 78% for men and 66% for women. Positive working climate was a major factor in choosing a GP practice. Most participants projected a career arc from employment to ownership or co-ownership of a practice within five years; only 7–9% preferred to remain employees. Conclusions Young and future GPs in Switzerland want to work part-time in small, GP-owned group practices. Practices should offer them employment opportunities with a path to (co-)ownership.